Modeling with digital ocean and digital coast - Zhang, Xin; Wang, Lei; Jiang, Xiaoyi; Zhu, Changming (Springer, 2017)
This book presents essential new insights in research and applications concerning spatial information technologies and coastal disaster prevention modeling for oceanic and coastal regions. As a new research domain of Digital Earth, it covers the latest scientific and technical advances, from the acquisition and integration of observational data, ocean spatio-temporal analysis and coastal flood forecasting to frequency modeling and the development of technical platforms. The individual chapters will be of interest to specialists in oceanic and coastal monitoring and management who deal with aspects of data integration, sharing, visualization, and spatio-temporal analysis from a Digital Earth perspective.
Keywords: Ocean -- Data processing.; Coasts -- Data processing.; Earth sciences -- Data processing.; Earth sciences -- Computer simulation.; Geodatabases.; Geographic information systems.; elektronické knihy; electronic books